Legal advice in the Public Administration (Universidad de San Andres Law Review, 2022)
The studies on public administration carried out in our country are usually partial studies, focused almost exclusively on the legal norms that regulate the administrative activity. Such a study can only achieve incomplete results, because public administration is much more than rules: there are behaviors, dynamics and inertias in it that are often not known. This administrative phenomenon is also present in the legal advisory function of the public administration, where not only legal rules are present.
Keywords: public administration; legal counseling; prior legal opinion; administrative reality